(untitled) (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
Education systems around the world have gone through many stages of development but perhaps the most important stage in the evolution of these systems is the integration of e-learning platforms into traditional education systems. Today, as never before, the importance of such distance learning tools comes to the fore when the world is facing with Covid 19 pandemic. The Faculty of Economics in Prilep had to adapt to those new conditions and teaching process last year was conducted on-line through a G suite for education tool. This e-learning platform is Google’s solution based on cloud computing concept. In this paper we will explore the perceptions of students at the Faculty of Economics in Prilep in terms of the benefits of e-learning faced by students in such a new situation where teaching took place completely on-line. For that purpose, a survey was conducted in which students from all study years were included. In this paper will be presented a statistical analysis for student’s perceptions about e-learning and their accordance for using this contemporary tool for teaching. The questionnaire was created with Google Forms and was delivered to students through the e mail. The main aim of this paper is to detect student’s perceptions about on-line teaching through this kind of e-learning platforms independently of their status in the faculty (year of study, department etc.). In the future, when creating and accrediting study programs, the recommendations contained in this paper could be taken into account in order to introduce e-learning as a one of the possible ways for realization of educational process.